AWWA G440-17 Emergency Preparedness Practices (PDF). - AWWA (American Water Works Association, 2017)
This standard covers the minimum requirements to establish and maintain an acceptable level of emergency preparedness based on the identified and perceived risks facing utilities within the water sector.